ARE VOCATIONAL SCHOOL STUDENTS READY TO FACE WORKFORCE DISRUPTION IN THE CONSTRUCTION FIELD? - Arfandi, Anas; Tahir Lopa, Akshari; Hasbi (Jurnal Pensil : Pendidikan Teknik Sipil, 2024)
The purpose of this research is to 1) Describe the digital literacy understanding of vocational high school students in the Construction and Property Engineering program. 2) Analyze students’ understanding of technological disruption in the field of construction. 3) Analyze students’ readiness to face technological disruptions in the construction field. The research was conducted at a vocational high school that offers the Construction and Property Engineering program in South Sulawesi province. The study took place from March to June 2023. The population of the research consisted of all students in grade X, totaling 1125 students. The sample size was determined using the Slovin formula with a 0.05 level of error, resulting in a sample of 318 respondents. All items are valid and reliable based on the validity and reliability test with a value greater than 0.361. The research findings indicate that the digital literacy understanding of vocational high school students in the Construction and Property Engineering program regarding their readiness to face the labor workforce disruption in the construction field is mostly categorized as very good with a percentage of 80%. Furthermore, students’ understanding of technological disruption in the construction field and their readiness to face the labor workforce disruption in the construction field is dominantly categorized as very good with a percentage of 63%. Student readiness is dominantly in the Able category, but there are still 18% who are in the Need to optimize category in facing technological disruption in the construction sector.